Will cities help us establish the Green Deal? - Boryczka, Ewa; Rzeńca, Agnieszka; Zasina, Jakub (W poszukiwaniu zielonego ładu, 2022)
The chapter focuses on the part cities might take in actions toward the European Green Deal. It starts with a presentation of contemporary urbanisation. It then explains the role cities have in sustainable development policy agendas. Next, the chapter features a review of current urban development concepts and tools. It concludes that cities have a transformative potential to solve environmental problems of global reach.